2017
DOI: 10.1590/s1808-185120171604174270
|View full text |Cite
|
Sign up to set email alerts
|

Workers' Compensation Is Associated With Worst Clinical Results After Lumbar Fusion

Abstract: Objective: The objective of this study was to evaluate the association of clinical results with preoperative situation of worker compensation (WC) in patients submitted to spine surgery. Methods: This was a retrospective, comparative, single center study. Patients who underwent lumbar spine arthrodesis were included. The outcomes were pain scores (VAS), physical constraint (ODI) and quality of life (EQ-5D). Outcomes were analyzed before surgery and after surgery (minimum follow-up of six months and maximum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Several studies have shown that musculoskeletal disorders are the main cause of long-term sickness absence; the most frequently encountered problem is low-back pain caused by cumulative trauma, and the source of this symptom could include inadequate postures during work activities, high physical demand of manual labor, and lack of rest pauses. 25 An association between manual labor professions and non-return to work after spine surgery is frequently reported, and available studies show even lower return-to-work rates (only 20% among manual labor workers) than those encountered in our work. 26 …”
Section: Discussionmentioning
confidence: 62%
“…Several studies have shown that musculoskeletal disorders are the main cause of long-term sickness absence; the most frequently encountered problem is low-back pain caused by cumulative trauma, and the source of this symptom could include inadequate postures during work activities, high physical demand of manual labor, and lack of rest pauses. 25 An association between manual labor professions and non-return to work after spine surgery is frequently reported, and available studies show even lower return-to-work rates (only 20% among manual labor workers) than those encountered in our work. 26 …”
Section: Discussionmentioning
confidence: 62%